Total corrosion management. Documentary analysis - Donadio, Michel; Capacho, Juan; Santander, Luis (Revista ALCONPAT, 2023)
The aim of this report is to provide a documentary analysis of the different corrosion mitigation techniques currently available, such as repair mortars, active and passive corrosion inhibitors, protective coatings and galvanic or induced current cathodic protection. These structures, built to last for a long time, are subject to ageing due to environmental influences such as water, atmospheric carbon dioxide and other harmful elements such as chlorides and pollution. The most common deterioration process in reinforced concrete structures is corrosion and subsequent expansion of the steel reinforcement, leading to cracking and spalling of the concrete.